Analisis Struktur Dan Kualitas Penulisan Abstrak Dalam Artikel Penelitian Tindakan Kelas - Adilah Kaharani Putri; Nanda Bilqist Amelia; Putri Sabrina; Mirna Majidatul Magfiroh; Imron Fauzi (Yayasan Al-Afif, 2026)
Writing an abstract is a crucial component of a scientific article because it serves as a brief summary of the research that determines whether readers will continue reading the entire article. However, many researchers, particularly in classroom action research publications, still struggle to compose abstracts that adhere to scientific writing structures and academic quality standards. This study aims to analyze the challenges of abstract writing in scientific papers through a systematic review of the structure and quality of writing reported in various previous studies. This study employed a systematic literature review (SLR) method to synthesize empirical findings regarding abstract writing practices in scientific works. The literature search was conducted using the Scopus and Google Scholar databases, employing a combination of keywords in the titles, abstracts, and article keywords. A total of 15 articles published between 2018 and 2023 were analyzed. The literature selection process involved the stages of identification, screening, eligibility assessment, and inclusion based on criteria of topic relevance, publication quality, and alignment with the research focus. The analysis focused on identifying issues related to the rhetorical structure of the abstract, the clarity of the research objectives, the completeness of the research method description, the presentation of research results, and the overall quality of writing. The results of the study indicate that there is still inconsistency in the use of abstract structure, a lack of clarity regarding objectives and methods, and limitations in presenting research results concisely and informatively.